Automatic lecturer status (in/out) via SMS / Megat Mohd Hafiz Megat Mohd Haniff - Megat Mohd Haniff, Megat Mohd Hafiz (2005)
The development of GSM Networks and terminals to support more advanced data bearer technologies has allowed for the introduction of new exciting data services. These technologies allow for a greater bandwidth and more capable execution environment, so permitting for the development of mobile applications. The world has become increasingly computer centric and computer applications are now used for a number of tasks such as communications, financial management, information retrieval, entertainment and game playing. The automatic lecturer status (in/out) via SMS is aimed to provide convenience way for student to know about availability of lecturer in their room at that time. It would have great significance on the students and the lecturers. This system will send automatic lecturer status (in/out) via SMS to the student's mobile phone based on lecturer status. Any mobile phones model in market that can send and receives SMS can be used with this system. A questionnaire was given to the students in order to get their opinion on the current system and their comment after using automatic lecturer status (in/out) via SMS. The completed application is running on Windows 2000 Professional.